Lack of Serological and Molecular Association between Toxoplasma Gondii Exposure and Obesity: A Case-Control Study - Alvarado-Esquivel, Cosme (Int J Biomed Sci, 2017)
The association between T. gondii infection and obesity has been scantly studied. Through an age-, and gender-matched case-control study, we determined the association of T. gondii infection and obesity using serological and molecular methods. Cases included 203 persons with obesity, and controls included 203 persons without obesity. Participants were tested for the presence of anti-Toxoplasma IgG antibodies using an enzyme-linked immunoassay (EIA). IgG seropositive individuals were further tested for the presence of anti-T. gondii IgM antibodies using an EIA, and T. gondii DNA by polymerase chain reaction (PCR). Anti-T. gondii IgG antibodies were found in 16 (7.9%) of the 203 cases and in 18 (8.9%) of the 203 controls (OR=0.87; 95% CI: 0.43-1.77; P=0.72). One (6.3%) of the 16 anti-T. gondii IgG seropositive cases and 6 (33.3%) of the 18 anti-T. gondii IgG seropositive controls were positive for IgM (P=0.09). Mean body mass index (35.5 ± 4.5) in T. gondii seropositive cases was similar (P=0.57) to that (36.1 ± 4.5) found in T. gondii seronegative cases. Stratification by obesity classes (I, II, and III) did not reveal differences (P>0.05) in seroprevalences (7.8%, 7.9%, and 8.1%, respectively) or high (>150 IU/ml) IgG antibody levels (3.3%, 3.9%, and 2.7%, respectively). PCR was positive in 5 (31.3%) of 16 cases, and in 5 (27.8%) of 18 controls examined (P=1.0). We found no serological or molecular evidence of an association between T. gondii infection and obesity in people attending a public health center in the northern Mexican city of Durango.